2016
DOI: 10.1016/j.corsci.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ppb levels of chloride impurities on the stress corrosion crack growth behaviour of low-alloy steels under simulated boiling water reactor conditions

Abstract: The effect of chloride on the stress corrosion crack (SCC) growth behaviour in low-alloy reactor pressure vessel steels was evaluated under simulated boiling water reactor conditions. In normal water chemistry environment, ppb-levels of chloride may result in fast SCC after rather short incubation periods of few hours. After moderate and short-term chloride transients, the SCC crack growth rates return to the same very low high-purity water values within few 100 hours. Potential long-term (memory) effects on S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…A number of researchers have found that the occurrence of pitting corrosion was an important contributing factor in crack initiation during the process of SCC . Furthermore, many other researchers have shown that the temperature of maximum SCC susceptibility is between 80–120 °C .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of researchers have found that the occurrence of pitting corrosion was an important contributing factor in crack initiation during the process of SCC . Furthermore, many other researchers have shown that the temperature of maximum SCC susceptibility is between 80–120 °C .…”
Section: Resultsmentioning
confidence: 99%
“…Most of the published research to‐date on pitting and stress corrosion cracking (SCC) are based on single mode or uniaxial loading of the material in CO 2 /H 2 S or chloride environment. Test results from four‐point bend specimens of austenitic stainless steel in chloride environment showed increased susceptibility to pitting corrosion with increased pre‐existing surface roughness or damage while compact tension test results in simulated boiling water reactor conditions showed that ppb level of chloride may result in fast SCC of low alloy steels . SCC of 22 and 25Cr SDSS under evaporative seawater conditions using uniaxial tensile specimen has been shown to depend on the level of applied stress and the test temperature; as the applied stress increased the threshold temperature for corrosion and cracking decreased .…”
Section: Introductionmentioning
confidence: 97%
“…In the past, the focus was placed on the effect of water chemistry transients on SCC in stainless steels [33][34][35][36][37] and these investigations clearly revealed that low concentration levels of sulphate and chloride (> 5 to 10 ppb) can result in significant acceleration of SCC crack growth in BWR normal water chemistry (NWC) environment. In recent investigations by Paul Scherrer Institut (PSI) [23][24][25] and General Electric Global Research (GE GR) [26], a tremendous effect of small amounts of chloride in the ppb concentration range was observed on the SCC growth behaviour of low-alloy RPV steels in simulated, highly oxidizing BWR NWC environment. In this environment, even small amounts of chloride (≥ 3 ppb) may result in acceleration of the SCC crack growth by one to three orders of magnitude after rather short incubation periods of a few hours [25].…”
Section: Lwr Operation Conditionmentioning
confidence: 99%
“…In recent investigations by Paul Scherrer Institut (PSI) [23][24][25] and General Electric Global Research (GE GR) [26], a tremendous effect of small amounts of chloride in the ppb concentration range was observed on the SCC growth behaviour of low-alloy RPV steels in simulated, highly oxidizing BWR NWC environment. In this environment, even small amounts of chloride (≥ 3 ppb) may result in acceleration of the SCC crack growth by one to three orders of magnitude after rather short incubation periods of a few hours [25]. The accelerated, fast SCC crack growth rates in the range of 10 -9 m/s to 10 -8 m/s hereby approached the high-sulphur SCC crack growth curve of the Ford & Andresen model [27,28].…”
Section: Lwr Operation Conditionmentioning
confidence: 99%
See 1 more Smart Citation